HISTORICAL / DOCUMENTARY REPRESENTATION OF THE TEACHER THEME IN CONTEMPORARY MONGOLIAN LITERATURE - Narmandakh Baasanjargal (International Journal of Innovative Technologies in Social Science, 2025)
This study examines how the portrayal of historical figures—specifically teachers—in contemporary Mongolian literature draws on both factual/historical materials and artistic imagination. Memoirs that recall historical personalities, and contemplative musings that express longing, help to consolidate the possibility of rendering historical figures into canonical form in literary works. The degree to which a literary work reflects actual historical events depends significantly on the individual author’s disposition: some are willing to modify documentary excerpts, while others strictly adhere to them.